Analisis Peran Auditor Internal Terhadap Kualitas Laporan Keuangan Studi Kasus pada LAZNAS Dewan Da’wah - Fadilla Qusnul Khotimah; Amrizal; Saiful Anwar; Dea Gusneli; Hardi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Good financial statements aid decision-making by ensuring that they are clear and trustworthy to stakeholders. Internal auditors play a very important role in this regard to ensure that financial statements are prepared correctly and in accordance with applicable regulations. This study aims to determine how the role of internal audit affects the quality of financial statements at LAZNAS Dewan Da'wah. Internal auditors are responsible for ensuring that the organization's financial statements are clear, accurate, and in accordance with applicable accounting principles. Therefore, the quality of financial statements must be considered because it affects the decision making of stakeholders. Currently, the role of internal audit is considered as one of the important roles in improving the quality of financial statements. This research uses a qualitative approach, which allows researchers to provide a better picture of the phenomenon in the field. The data collection techniques used in this research are interviews and documentation. The analysis technique used is descriptive analysis technique. Data analysis is done by collecting, selecting raw data, processing and interpreting the data obtained. The results showed that the quality of financial statements was significantly influenced by internal audit. Internal auditors can evaluate and understand financial reports to overcome problems, and good management can overcome problems in the internal accounting system and maintain accurate financial reporting. Effective communication and systematization also contribute to the efficiency and improvement of auditors.